2022
DOI: 10.3138/ptc-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Physiotherapeutic Interventions for Trismus in Head and Neck Cancer: Where Is the Manual Therapy?

Abstract: Purpose: Trismus, or restricted mouth opening, is a common side effect of treatment for head and neck cancer. This scoping review examined the characteristics, extent, and nature of existing research on manual therapy and jaw-mobilizing devices to prevent and manage trismus related to head and neck cancer. Method: Six electronic databases were searched using the terms trismus, head and neck cancer, and physical therapy and the associated MeSH terms. The review focused on the factors related to intervention del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Dijsktra et al 18 also reported on a retrospective case series examining exercise and various physical therapy techniques. Nedeljak et al 19 highlighted the MT knowledge gap in their recent review of MT interventions in the HNC population. This study aims to demonstrate that MT can be considered either as a frontline or adjuvant treatment for radiationinduced trismus.…”
mentioning
confidence: 99%
“…Dijsktra et al 18 also reported on a retrospective case series examining exercise and various physical therapy techniques. Nedeljak et al 19 highlighted the MT knowledge gap in their recent review of MT interventions in the HNC population. This study aims to demonstrate that MT can be considered either as a frontline or adjuvant treatment for radiationinduced trismus.…”
mentioning
confidence: 99%